Impact of mitochondria on nitrite metabolism in HL-1 cardiomyocytes - Dungel, Peter; Teuschl, Andreas H.; Banerjee, Asmita; Paier-Pourani, Jamile; Redl, Heinz; Kozlov, Andrey V. (Frontiers in Physiology, 2013)
Apart from ATP synthesis mitochondria have many other functions, one being nitrite reductase activity. NO released from nitrite has been shown to protect the heart from ischemia/reperfusion injury in a cGMP-dependent manner. However, the exact impact of mitochondria on the release of NO from nitrite in cardiomyocytes is not completely understood. Besides mitochondria, a number of non-mitochondrial metalloproteins have been suggested to facilitate this process. The aim of this study was to investigate the impact of mitochondria on the bioactivation of nitrite in HL-1 cardiomyocytes. The levels of nitrosyl complexes of hemoglobin (NO-Hb) and cGMP levels were measured by electron spin resonance spectroscopy and enzyme immunoassay. In addition the formation of free NO was determined by confocal microscopy as well as intracellular nitrite and S-nitrosothiols by chemoluminescence analysis. NO was released from nitrite in cell culture in an oxygen dependent manner. Application of specific inhibitors of the respiratory chain, p450, NO synthases and xanthine oxidoreductase showed that all four enzymatic systems are involved in the release of NO, but more than 50% of NO is released via the mitochondrial pathway. Only NO released by mitochondria activated cGMP synthesis. Cardiomyocytes co-cultured with red blood cells (RBC) competed with RBC for nitrite, but free NO was detected only in HL-1 cells suggesting that RBC are not a source of NO in this model. Apart from activation of cGMP synthesis, NO formed in HL-1 cells diffused out of the cells and formed NO-Hb complexes. In addition nitrite was converted by HL-1 cells to S-nitrosyl complexes. In HL-1 cardiomyocytes, several enzymatic systems are involved in nitrite reduction to NO but only the mitochondrial pathway of NO release activates cGMP synthesis. Our data suggest that this pathway may be a key regulator of myocardial contractility especially under hypoxic conditions.